Designing E-Commerce Applications for Mobile-Based Audioo Technics Stores - Muhammad Fajar Fikri; Nurul Hamdi (Brilliance: Research of Artificial Intelligence, 2023)
It seems that existing technological advances have not been utilized equally by business actors, one of which is the Audi Technics Store. Audio Technics Shop is an electronics shop that sells various audio-based tools. In its marketing activities, this shop still uses a conventional marketing system which is carried out directly through the shop. The obstacle faced is the difficulty of reaching a wider range of customers. This research aims to design a mobile-based AudioTech e-commerce application that can be accessed online by customers at the Audio Technics Store. This research produces a conclusion that the mobile-based e-commerce application designed for the Audio Technics Store can help product marketing and product sales activities online and more widely.